Proceedings of the 7th International Conference on Computational Systems-Biology and Bioinformatics 2016
DOI: 10.1145/3029375.3029377
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency Noise Attenuation of a Two-component System Responding to Short-pulse Input

Abstract: Among the various biological devices developed and characterized in synthetic biology, light-sensing biological devices can serve as an input-output system owing to their light modulation property. The well-characterized devices in living systems are useful for modulating cellular sensing and transducing information. In this study, we examined short pulse responsiveness of a light-sensing two-component system (TCS), Cph8-OmpR, which was generated by replacing the sensor domain of the EnvZ-OmpR osmoregulatory s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In CcaS-CcaR v2.0, systematic investigations have shown that the pathway switching is relatively insensitive to CcaS abundance: the amount of CcaS should be above the lowest level and below the limiting of PCB; as for PCB production, the same study tested a series of promoters to control the transcription level of hoI and pcyA , among which the J 23108 promoter led to the best dynamic range without causing cell toxicity or spontaneous mutation in this part of the circuit. Meanwhile, mathematical models , and experiments suggested that the CcaR level is crucial for an enhanced dynamic range in CcaS–CcaR TCS. Based on such knowledge, we decided to retain the levels of CcaS and PCB in CcaS-CcaR v2.0 as they were already optimized in E.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CcaS-CcaR v2.0, systematic investigations have shown that the pathway switching is relatively insensitive to CcaS abundance: the amount of CcaS should be above the lowest level and below the limiting of PCB; as for PCB production, the same study tested a series of promoters to control the transcription level of hoI and pcyA , among which the J 23108 promoter led to the best dynamic range without causing cell toxicity or spontaneous mutation in this part of the circuit. Meanwhile, mathematical models , and experiments suggested that the CcaR level is crucial for an enhanced dynamic range in CcaS–CcaR TCS. Based on such knowledge, we decided to retain the levels of CcaS and PCB in CcaS-CcaR v2.0 as they were already optimized in E.…”
Section: Discussionmentioning
confidence: 99%
“…promoters to control the transcription level of hoI and pcyA, among which the J23108 promoter led to the best dynamic range without causing cell toxicity or spontaneous mutation in this part of the circuit. Meanwhile, mathematical models 32,33 and experiments 12 suggested that the CcaR level is crucial for an enhanced dynamic range in CcaS−CcaR TCS. Based on such knowledge, we decided to retain the levels of CcaS and PCB in CcaS-CcaR v2.0 as they were already optimized in E. coli previously.…”
Section: ■ Discussionmentioning
confidence: 99%
“…A high dynamic range indicates strong effects when "switched on" and low leakage when "switched off". Mathematic models 31,32 and experiments 11 suggested that CcaR level is crucial for enhanced dynamic range in CcaS-CcaR TCS. In this study, we tested a series of CcaR expression levels to find the best dynamic range for optoCRISPRi-HD.…”
Section: Discussionmentioning
confidence: 99%